Opioid Use in Palliative Care: A Qualitative Study and Assessment of Patients’ Quality of Life at Anutapura Hospital, Palu, Indonesia. - Fyolla Patricia Panto; Aresh Bilal; Afriani Kusumawati; Ririn Hardani; Eny Kustiowaty; Irnayanti Irnayanti; Rudi Safarudin (Generics: Journal of Research in Pharmacy, 2026)
Palliative care, being the state of care dealing with patients with terminal conditions often utilizes opioid analgesics to manage the moderate and severe pain endured by the patients. Despite their powerful painkiller, opioids are notorious for their negative consequences on several aspects of the users’ health. To investigate the knowledge, perceptions, and experiences, as well as the quality of life of patients receiving opioids in palliative care. This study is a descriptive qualitative design with a phenomenological approach. Of the 14 opioid users identified between 2023-2024 in palliative setting, with purposive sampling approach, we recruited 5 (five) eligible patients who were willing to participate in the study. We interviewed the patients using the developed questionnaire, referencing the existing published opioid qualitative literature. The eight qualitative questionnaire domains were: (1) Pain/physical ailments (2) Resources/Support system, (3) Knowledge and Awareness of The Medication, (4) Functionality, Autonomy, and Mobility, (5) Physical, Emotional, and Psychological health, (6) Coping/Resources, (7) Feeling of security in treatment, (8) Hope. Furthermore, we added patients’ clinical data from the medical records, and quality of life measured with the SF-12 questionnaire. It is worth noticing that the patients perceived inadequate information about the holistic aspects of opioid use. Regardless, the patients still found that the opioids were viable for their pain management. However, they were still somehow worried about the side effects of the drugs. In general, judging from the SF-12 measurement, the patients had good health conditions. Despite the viability of the drugs in pain management, participants' knowledge of opioids as strong analgesics could still be improved. The opioid users were also still concerned about addiction, physical dependence, and other side effects. Overall, the patients felt the opioids’ benefits, as shown by their relatively good health conditions and quality of life.